Konstytucja w praktyce sądów administracyjnych - Kiczka, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The Constitution is directly applied by administrative courts. Constitutional regulations are the basis for shaping the control pattern. The pro-constitutional interpretation of law is of great importance. The direct application of the Constitution by the administrative courts concerns different matters and serves to ensure the rule of law in the executive branch activities
Keywords: administracja publiczna; prawo konstytucyjne; sądowa kontrola administracji; sądownictwo administracyjne